로버스트 그룹 독립성분분석 - 김현성; Hyunsung Kim; 이웅주; Xiongzhu Li; 임예지; Yaeji Lim (Ŭngyong tʻonggye yŏnʼgu, 2021)
독립성분분석은 혼합 데이터로부터 독립된 신호들을 분리해내는 대표적인 통계적 방법론이며, 그룹 독립성분분석은 독립성분분석을 여러 개체에 적용할 수 있도록 확장한 방법론이다. 그룹 독립성분분석은 기능적 자기 공명 영상 데이터에 활용되어 의학적으로 유의미한 결과를 줌이 알려져있다. 그러나 자기 공명 영상 스캔에서 흔히 일어나는 이상치가 포함되어 있는 경우, 기존의 그룹 독립성분분석은 그 효과가 떨어짐이 알려져있다. 본 연구에서는 ROBPCA 기반의 로버스트한 그룹 독립성분분석 방법론을 제안하였다. 시뮬레이션과 실제 자료 분석을 통해 제안한 방법과 기존 방법을 비교하였고, 그 결과 제안한 방법론의 로버스트성을 입증했다. Independent Component Analysis is a popular statistical method to separate independent signals from the mixed data, and Group Independent Component Analysis is an its multi-subject extension of Independent Component Analysis. It has been applied Functional Magnetic Resonance Imaging data and provides promising results. However, classical Group Independent Component Analysis works poorly when outliers exist on data which is frequently occurred in Magnetic Resonance Imaging scanning. In this study, we propose a robust version of the Group Independent Component Analysis based on ROBPCA. Through the numerical studies, we compare proposed method to the conventional method, and verify the robustness of the proposed method.